Information: on the question as for the meaningful evolution of the term - O. S. Bakumov; M. I. Marchuk; T. I. Gudz; О. О. Venglinskyi (Law and Safety)
Information as a certain terminological concept of evolutionary nature and interdisciplinary significance is analyzed. At the same time, given the objectives of the study, it is considered as an object that requires proper legal understanding and appropriate regulatory (primarily constitutional and legal) regulation. The role of information as one of the main resources used by a person in the process of his activity is noted.